Expression of arylamine N-acetyltransferase in human intestine. Issue 3 (1st March 1998) - Hickman, D; Pope, J; Patil, S D; Fakis, G; Smelt, V; Stanley, L A; Payton, M; Unadkat, J D; Sim, E
Abstract : Background —Arylamine N -acetyltransferases in humans (NAT1 and NAT2) catalyse the acetylation of arylamines including food derived heterocyclic arylamine carcinogens. Other substrates include the sulphonamide 5-aminosalicylic acid (5-ASA), which is an NAT1 specific substrate; N -acetylation of 5-ASA is a major route of metabolism. NAT1 and NAT2 are both polymorphic. Aims —To investigate NAT expression in apparently healthy human intestines in order to understand the possible role of NAT in colorectal cancer and in the therapeutic response to 5-ASA. Methods —The intestines of four organ donors were divided into eight sections. DNA was prepared for genotyping NAT1 and NAT2 and enzymic activities of NAT1 and NAT2 were determined in cytosols prepared from each section. Tissue was fixed for immunohistochemistry with specific NAT antibodies. Western blotting was carried out on all samples of cytosol and on homogenates of separated muscle and villi after microdissection. Results —NAT1 activity of all cytosols was greater than NAT2 activity. NAT1 and NAT2 activities correlated with the genotypes of NAT1 and NAT2 and with the levels of NAT1 staining determined by western blotting. The ratio of NAT1:NAT2 activities showed interindividual variations from 2 to 70. NAT1 antigenic activity was greater in villi than in muscle. NAT1 was detected along the length of the villi in the small intestine. In colon samples there was less NAT1 at the base of the crypts with intense staining at the tips. Conclusions —The interindividual variation in NAT1 and NAT2 in the colon could affect how individuals respond to exposure to specific NAT substrates including carcinogens and 5-ASA.